Journal of Stomatology is „J Stoma” - LOSTER, Bartłomiej (Journal of Stomatology, 2015)
The advent of 2015 marks the new beginning for our periodical. We are the leading dental scientific publication in Poland. We maintain a standard that requires scrupulous observation of publishing guidelines. It is reflected in the number of rejected papers at around 18%. Our periodical is indexed in the Scopus international electronic database. Until the end of 2014, all the papers were published in two languages: English and Polish. As of this year, all the original papers can be published in the English language only. We control a fully electronic circulation of papers based on the Index Copernicus International.The official abbreviation of the Journal of Stomatology is “J Stoma”, and although The National Library uses the “J Stomatol” abbreviation, “J Stoma” is by all means appropriate. Search engines correctly recognize “stoma” as part of the abbreviation, as it does for “j stoma”. “J Stoma” is contained in “J Stomatol”. The abbreviation has functioned for a couple of years; its change might result in errors when citations are counted, and their omissions. The “J Stomatol” abbreviation functions exclusively in The National Library catalogue and its data are not exported to other libraries or databases. Authors can cite papers from the following sources: printed material, electronic publications and information repositories, namely databases, and there the J Stoma abbreviation has already been present for a long time. The ISSN abbreviation is merely for registration purposes.